Acupuncture for Relieving Abdominal Pain and Distension in Acute Pancreatitis: A Systematic Review and Meta-Analysis - Zhu, Fengya; Yin, Shao; Zhu, Xinyun; Che, Deya; Li, Zimeng; Zhong, Yue; Yan, Hui; Gan, Daohui; Yang, Lanying; Wu, Xiaohan; Li, Liuying (Frontiers in Psychiatry, 2021)
Background: Clinical evidence suggests that acupuncture is effective for relieving abdominal pain and distension in acute pancreatitis (AP). However, there is a lack of systematic reviews and meta-analyses that provide high-quality evidence of the efficacy and safety of acupuncture in this context. Aim: To assess the efficacy and safety of acupuncture for relieving abdominal pain and distension in AP. Methods: We searched the PubMed, Web of Science, Embase, Cochrane Library, CNKI, Wanfang, VIP, and China Biomedical Literature databases. Randomized controlled trials of acupuncture plus routine treatment (RT) vs. RT alone or RT plus sham/placebo acupuncture were included. Primary outcomes included total effectiveness rate, VAS scores for abdominal pain and distension, and time until relief of abdominal pain and distension. Secondary outcomes included time until recovery of bowel sound, time until first defecation, length of hospital stay, and APACHE II score. Results: Nineteen eligible original studies (n = 1,503) were included. The results showed that acupuncture in combination with RT had a significant advantage in terms of increasing the total effectiveness rate [risk ratio: 1.15; 95% confidence interval (CI): 1.06–1.24; P = 0.001]. Acupuncture also reduced the VAS score for abdominal pain [weighted mean difference (WMD): −1.45; 95% CI: −1.71 to −1.19; P < 0.0001] and the VAS score for abdominal distension (WMD: −0.71; 95% CI: −1.04 to −0.37; P < 0.0001) in patients with AP. Other results also showed the efficacy of acupuncture. One study reported adverse events after acupuncture. Conclusion: Acupuncture in combination with RT has a better effect than RT alone for relieving abdominal pain and distension in AP. More rigorous studies are needed to confirm this result. Systematic Review Registration: PROSPERO CRD42019147503 (https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=147503).